STAT1 single nucleotide polymorphisms and susceptibility to immune thrombocytopenia. (August 2015) - Chen, Zhenping; Guo, Zhenxing; Ma, Jingyao; Liu, Fuhong; Gao, Chao; Liu, Shuguang; Wang, Ami; Wu, Runhui
Abstract Primary immune thrombocytopenia (ITP) is an acquired autoimmune bleeding disorder. One of the key mediators of IFN-γ signaling is the signal transducer and activator of transcription 1 protein (STAT1). We evaluated the relationship between STAT1 gene single nucleotide polymorphisms (SNPs) and the associated risk of ITP in a prospective case–control study. A total of 548 children were recruited: 328 children with ITP and 220 healthy children as sex- and age-matched normal controls. The Sequenom MassArray system (Sequenom, San Diego, CA) was used to detect three SNPs genotypes in the STAT1 gene: rs10208033, rs12693591, and rs1467199. There is a statistically significant difference in STAT1 rs1467199 allele frequencies with comparison of each of the four clinical subgroups of ITP patients to the normal controls (p = 0.0432). Also, newly diagnosed ITP patients and chronic ITP patients demonstrate significant different genotypes (χ2 = 8.511, p = 0.0142) and allelic frequency (p = 0.0055). Although a positive STAT1 rs1467199 genotype subgroups to the STAT1 mRNA expression level cannot be established, there is a weak correlation between STAT1 mRNA level and the activity ratio of Type 1 T helper lymphocyte and Type 2 T helper lymphocyte (Th1/Th2 ratio) (p = 0.0544); correlation with IFN-γ alone did not reach statistical significance (p = 0.1715). The findings in our study suggest that STAT1 rs1467199 SNP plays a potential role in the IFN-γ dependent development of autoimmunity in children with ITP. The important clinical implication of STAT1 SNPs testing as a predictor of pediatric chronic ITP will be validated in future molecular and protein functional analysis.